Applying ITIL Framework to Analyze Problem Management Key Performance Indicator (KPI): a Case Study of Malay Owner Company (Mesiniaga Berhad) - Mokhsin, Mudiana; Shakir Zainol, Amer; Nordianah Haihom, Siti; Husni Mohd Som, Mohd; Jalil Abdul Rahim, Abdul (International Journal of Engineering and Technology, 2018)
Problem Management (PM) is one of the components in the Information Technology Infrastructure Library (ITIL) Service Support area. The primary focus of Problem Management is to identify causes of service issues and commission corrective work to prevent recurrences. To address this practice and make it more effective, the project tends to identify the specific Key Performance Indicator (KPI) for     Problem Management process in a Malay owner company named as Mesiniaga Berhad. The identification of Problem Management KPI is based on the previous research which is using ITIL as a framework. The interview session has been conducted in Mesiniaga with Problem Manager working at that company with more than 10 years’ experience in Problem Management process. The method of     interview is using qualitative approach which is using the design question with the lists of KPI. The expert will select or decide which KPI are related with the current report in Mesiniaga. The result showed that 6 KPIs are related and come out with analysis on how the outcome of KPI behavior matched with the Incident report in Mesiniaga. To enhance on how the identification of KPI, instead of using manual to capture the Problem Management KPI, the automation of selected KPI from Incident to Problem Management can be        implement in the systems. Most technologies are intelligent enough for data analytic to decide which suitable KPI of Problem           Management follow the current business and client environment.